Introducing the Reshape strategy: Preserving material integrity - Sander, Nikoline; Larsen, Linda Nhu (Proceedings of the 6th Product Lifetimes and the Environment Conference (PLATE2025), 2025)
One of the significant challenges of today’s society is the unsustainable overconsumption of resources, coupled with the generating of enormous amounts of waste. European manufacturing produces over 230 million tons of waste annually, much of which remains unaddressed within existing circular economy frameworks that predominantly focus on post-consumer waste. This paper introduces the Reshape strategy, which aims to respect, incorporate, and utilise pre-consumer industrial waste to create new products, thereby reducing dependence on virgin materials. Positioned within current R-frameworks, the Reshape strategy addresses a theoretical gap in circular economy literature, where the Recycling strategy is commonly used and Reuse often being misapplied, leading to theoretical ambiguity. Reshaping emphasises the extension of material lifetimes rather than downcycling through recycling. Therefore, this research explores the potential of industrial waste as a resource through 19 case studies from a Danish research project focused on designing with industrial waste materials. The findings emphasise the inherent qualities of industrial waste and outline activities within the Reshape strategy that leverage the material’s integrity in terms of function, form, or material composition, thereby extending its lifetime. By leveraging these qualities, this study contributes theoretically to the circular economy by refining terminology and advancing the understanding of pre-consumer waste within circular systems. The Reshape strategy aligns with circular economy principles, aiming to keep materials in productive loops while addressing the significant untapped potential of discarded materials.